Admissibility in a Court of Law of Illegally Obtained Evidence and the Right to Privacy: Examining the Impact of Legislative Safeguards on Admissibility of Illegally Obtained Evidence and the Right to Privacy in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
When it comes to safeguarding an individual's right to privacy from unreasonable search andseizure inside the course of gathering evidence, India falls far short of legislative safeguards. Both theoffender and the victim have specific rights and safeguards in criminal cases. To be admissible, evidencemust now meet just one criteria be relevant. Certain cases may suffer from extreme unfairness becausethere are no regulations prohibiting the introduction of evidence that was acquired illegally. The LawCommission of India conducted a detailed study that proposed changes to the Indian Evidence Act.Despite this, the Law Commission's recommendations were never put into practise.